KNOWLEDGE OF DRUG MANAGEMENT OFFICERS AND DRUG AVAILABILITY AT PRIMARY HEALTH CENTERS IN MAKASSAR CITY - Andi Paluseri; yuniati; Lukman Lukman (Jurnal Kesehatan Yamasi Makassar, 2026)
Adequate drug availability at primary health centers (Puskesmas) is a key indicator of effective drug management and may be influenced by the knowledge of drug management officers. This study aimed to examine the relationship between officers’ knowledge and drug availability at selected Puskesmas in Makassar City. A descriptive analytical observational study with a cross-sectional design was conducted on May 16–17, 2025, at Paccerakkang, Mamajang, Pattingalloang, and Mangasa Puskesmas, which were selected using cluster random sampling. All eligible drug management officers were included through total sampling, resulting in seven respondents. Knowledge was assessed using a 20-item questionnaire with excellent reliability (Cronbach’s alpha = 0.9675), while drug availability was evaluated using 2024 Drug Usage and Request Reports (LPLPO) for 40 indicator drugs. Data were analyzed using the Shapiro–Wilk normality test and Pearson’s correlation test. The mean knowledge score was 90%, categorized as good; six respondents had good knowledge and one had sufficient knowledge. Drug availability varied across facilities: one Puskesmas was categorized as good (69.87%), while three were categorized as sufficient, with an average availability of 46.29%. Pearson’s correlation showed no significant relationship between officers’ knowledge and drug availability (r = -0.853; p = 0.147). These findings suggest that drug availability is likely influenced more by procurement policies, distribution systems, and health budget allocation than by officers’ knowledge alone.